UiTM student’s attendance system based on biometric fingerprint with IoT implementation / Wan Muhammad Rahimi Wan Fadzli, Abidah Mat Taib - Wan Fadzli, Wan Muhammad Rahimi; Mat Taib, Abidah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The use of biometric technology in attendance systems has become increasingly popular in recent years, as it provides a convenient and secure way to record attendance. This project aims to develop a biometric fingerprint-based attendance system for students of Universiti Teknologi Mara (UiTM). The system will be integrated with IoT technology to improve its accessibility and data management capabilities. The current manual attendance system used for most universities is prone to errors and lacks efficient record keeping and monitoring capabilities. This results in difficulties for both the students and the lectures in tracking attendance records. As a result of this issue, the purpose of this research is to develop a student’s attendance system with biometric authentication features more correctly without the need for lecturers to manually track attendance. Lecturers can collect all the attendance records of each user details as well as incoming & outgoing timing. The data can also be downloaded and exported to an excel sheet. The system will trace the absent user, and user who does not attend more than three times or six times without medical certificate (MC) will receive a warning. The system was evaluated by 30 respondents as a form of User Acceptance Testing (UAT) and theresults show that the majority agreed that the system is achieved the perceived ease of use and perceived usefulness. The project includes the design, development, and testing of the system, as well as a user evaluation to assess its effectiveness.